Taxonomic and nomenclatural revision of Carlos Pau’s names in Hieracium (Asteraceae) - Ferrer-Gallego, P. Pablo; Mateo, Gonzalo; Gavioli, Laura; Ibáñez, Neus (Phytotaxa, 2019)
During a study on the taxonomy of Hieracium for the Flora iberica project, several names turned out to be not yet typified. In the present paper, 63 names of Hieracium are treated. In order to fix their applications, nomenclatural types for 28 Pau’s names in the genus Hieracium are designated (27 lectotypes, 1 neotype and 1 epitype). All the type material available is listed with full label data, and some nomenclatural and taxonomic comments are provided.